Diversifying rice-centric agriculture and diets: The Bangladesh experience - Ahmed, Akhter; Ghostlaw, Julie (International Food Policy Research Institute, 2019)
This chapter reviews recent policy developments in agriculture and nutrition in Bangladesh, and then draws upon household-level data to examine trends related to agricultural production, food consumption and nutrition, and women’s empowerment. Using this evidence, the authors present a government-led experiment that is working towards filling critical knowledge and action gaps for promoting nutrition-sensitive agriculture. Bringing together this evidence, they conclude that identifying, developing, and supporting synergies among the agriculture, nutrition, and health sectors is critical for Bangladesh to improve food and nutrition security.